2018
DOI: 10.1101/369652
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Object-based attention prioritizes working memory contents at a theta rhythm

Abstract: Attention samples spatial positions, visual objects or auditory streams rhythmically. This has been reported for tasks where the attended information was perceptually present. Here we tested whether attentional sampling also applies to internal representations held in working memory. Participants memorized four spatial positions that formed the endpoints of two objects, one of which was cued for a delayed match-non-match test. When uncued positions were probed, participants responded faster to those located on… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 69 publications
2
6
0
Order By: Relevance
“…Our results of an attentional sampling at non-cued locations in the behaviourally relevant cue condition fits well with findings reporting that the 7-to 8-Hz frequency is most often found when attention is undivided and directed to one location only, as found in electrophysiological studies (Busch et al, 2009;Busch & VanRullen, 2010). Curiously, whereas earlier studies found that non-cued locations on the same object and the different object were sampled in an anti-phasic pattern (Fiebelkorn et al, 2013;Peters et al, 2020), we rather found a phase-consistent pattern in this study.…”
Section: Characteristics Of Rhythmic Attention At Non-cued Locationssupporting
confidence: 91%
See 2 more Smart Citations
“…Our results of an attentional sampling at non-cued locations in the behaviourally relevant cue condition fits well with findings reporting that the 7-to 8-Hz frequency is most often found when attention is undivided and directed to one location only, as found in electrophysiological studies (Busch et al, 2009;Busch & VanRullen, 2010). Curiously, whereas earlier studies found that non-cued locations on the same object and the different object were sampled in an anti-phasic pattern (Fiebelkorn et al, 2013;Peters et al, 2020), we rather found a phase-consistent pattern in this study.…”
Section: Characteristics Of Rhythmic Attention At Non-cued Locationssupporting
confidence: 91%
“…reaction times) better capture rhythmic variability in behaviour. Both types have been used in rhythmic attention paradigms (Fiebelkorn et al, 2013;Landau & Fries, 2012;Peters et al, 2020). Furthermore, there is still no consensus on the best way to identify peaks in power spectra that result from behavioural time courses.…”
Section: Characteristics Of Rhythmic Attention At Non-cued Locationsmentioning
confidence: 99%
See 1 more Smart Citation
“…After a blank delay of 1000 ms we presented a cue for 250 ms that matched the color of either Stimulus A or Stimulus B and indicated which of the two working memory items will be probed with 75% validity. Based on previous studies we hypothesized that the cue would reset rhythmic attentional sampling while still requiring participants to maintain a representation of the un-cued item (Fiebelkorn et al, 2013; Landau & Fries, 2012; Mo et al, 2019; Peters et al, 2018). The cue was followed by a blank screen of variable delay (between 200 ms and 700 ms in steps of 16.6 ms) after which we presented a Probe stimulus for 75 ms that matched either Stimulus A or Stimulus B in color and was oriented slightly clock-wise or counter clock-wise.…”
Section: Methodsmentioning
confidence: 99%
“…Recent work has begun to extend the rhythmic nature of internal attention directed towards VWM items. Peters et al instructed participants to memorize four dots that defined the endpoints and hence the outlines of 2 objects (Peters et al, 2018). A subsequent retro-cue directed and reset attention to one of these objects.…”
Section: Introductionmentioning
confidence: 99%